KECERDASAN EMOSIONAL KHADIJAH AL-KUBRA R.A.:AWAL TEGAKNYA ISLAM - fatimah, sitti (An - Nisa`, 2010)
Abstract: Emotional Intellegence is psychological element capable that couse the owner to reach successfulness in all area. Islam is religion which always place forward the emotional intelligence importantly, so that islam always up to date. Kadijahâs emotional intelligence had accompanied her to become especial first woman supporter to islam development. Khadijaâs intelligence had coused her belonging a good attitude, action and behavior. Also, had become a power for rasulullah in the effort improve;repairing mankind by islam as a religion of tauhid. Rasulullah had mind power to get full support from khadija. By her intelligence, Khadijah had rendered all her energy, mind, and all properties for the evocation of islam.It can also be said that in the reality, the successfulness of Rasulullah to bring islam, that loaded with safety, there was a capable figure to give clarification of emotional intelligence fromÂ  a woman becoming the source of strength of Rasulullah in the early of the madding a night of it of islam, she was khadijah Al-Kubra R.A.So that, it is properly for Khadijah R.A that be performed as great woman or wonder woman. Also, it because she had get special greeting from the Allah SWT.